Kurikulum Pendidikan Anak Usia Dini dan Integrasi Nilai Multikultural - Azizah Hanum; Adinda Hasri; Afwany Amalia Hasibuan; Adenia Adenia (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
Early Childhood Education (PAUD) plays a crucial role in shaping children’s character, social attitudes, and life values from an early age. In Indonesia’s multicultural society, the PAUD curriculum must be developed to be responsive to diversity in culture, religion, language, and social background so that it can instill the values of tolerance, empathy, and mutual respect. This study aims to examine the development of an ECE curriculum responsive to diversity and the implementation of multicultural values in early childhood education. The research method employed is qualitative research using a literature review approach. Data were collected from books, scientific journals, and relevant literature, then analyzed using qualitative descriptive techniques. The results of the study indicate that the integration of multicultural values can be achieved through thematic learning, play activities, storytelling, role-playing, and the use of learning media that reflect diversity. The systematic implementation of the curriculum helps children understand and appreciate differences from an early age. Thus, a multicultural-based PAUD curriculum plays a crucial role in shaping a generation that is inclusive, tolerant, and capable of living harmoniously in a diverse society.